From discipline to control in nursing practice: A poststructuralist reflection - McIntyre, Jonathan R. S. (Nursing philosophy, 2020)
The everyday expressions of nursing practices are driven by their entanglement in complex flows of social, cultural, political and economic interests. Early expressions of trained nursing practice in the United States and Europe reflect claims of moral, spiritual and clinical exceptionalism. They were both imposed upon—and internalized by—nursing pioneers. These claims were associated with an endogenous narrative of discipline and its physical manifestation in early nursing schools and hospitals, which functioned as "total institutions." By contrast, the external forces—diffuse yet pervasive—impacting upon contemporary nursing more closely align with the power dynamics explored in Gilles Deleuze's concept of the Society of Control. The example of sensor technology and telemetric monitoring of nurses’ locations in the clinical setting exemplifies the intense presence of surveillance, performance metrics and the "rationalization" of nursing practice. It falls upon nurses to recognize, accept or challenge these dynamics in order to shape the future of nursing practice into a discipline which embodies our values and priorities.